Comparative cytogenetics of anembryonic pregnancies and missed abortions in human - T. V. Nikitina; E. A. Sazhenova; E. N. Tolmacheva; N. N. Sukhanova; S. A. Vasilyev; I. N. Lebedev (Вавиловский журнал генетики и селекции)
Miscarriage is an important problem in human reproduction, affecting 10–15 % of clinically recognized pregnancies. The cases of embryonic death can be divided into missed abortion (MA), for which the ultrasound sign of the embryo death is the absence of cardiac activity, and anembryonic pregnancy (AP) without an embryo in the gestational sac. The aim of this study was to compare the frequency of chromosomal abnormalities in extraembryonic tissues detected by conventional cytogenetic analysis of spontaneous abortions depending on the presence or absence of an embryo. This is a retrospective study of 1551 spontaneous abortions analyzed using GTG-banding from 1990 to 2022 (266 cases of AP and 1285 cases of MA). A comparative analysis of the frequency of chromosomal abnormalities and the distribution of karyotype frequencies depending on the presence of an embryo in the gestational sac was carried out. Statistical analysis was performed using a chi-square test with a p < 0.05 significance level. The total frequency of chromosomal abnormalities in the study was 53.6 % (832/1551). The proportion of abnormal karyotypes in the AP and MA groups did not differ significantly and amounted to 57.1 % (152/266) and 52.9 % (680/1285) for AP and MA, respectively (p = 0.209). Sex chromosome aneuploidies and triploidies were significantly less common in the AP group than in the MA group (2.3 % (6/266) vs 6.8 % (88/1285), p = 0.005 and 4.9 % (13/266) vs 8.9 % (114/1285), p = 0.031, respectively). Tetraploidies were registered more frequently in AP compared to MA (12.4 % (33/266) vs. 8.2 % (106/1285), p = 0.031). The sex ratio among abortions with a normal karyotype was 0.54 and 0.74 for AP and MA, respectively. Thus, although the frequencies of some types of chromosomal pathology differ between AP and MA, the total frequency of chromosomal abnormalities in AP is not increased compared to MA, which indicates the need to search for the causes of AP at other levels of the genome organization, including microstructural chromosomal rearrangements, monogenic mutations, imprinting disorders, and epigenetic abnormalities.